2014
DOI: 10.1038/ncomms6303
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study identifies multiple loci associated with both mammographic density and breast cancer risk

Abstract: Mammographic density reflects the amount of stromal and epithelial tissues in relation to adipose tissue in the breast and is a strong risk factor for breast cancer. Here we report the results from meta-analysis of genome-wide association studies (GWAS) of three mammographic density phenotypes: dense area, non-dense area and percent density in up to 7,916 women in stage 1 and an additional 10,379 women in stage 2. We identify genome-wide significant (P<5×10−8) loci for dense area (AREG, ESR1, ZNF365, LSP1/TNNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 42 publications
12
104
0
1
Order By: Relevance
“…Conversely, inhibition of signaling through estrogen receptors by Tamoxifen reduced mammographic density and was associated with decreased risk of subsequent breast cancer (Cuzick et al 2011). Identification of genes involved in estrogen signaling among the 11 loci associated with differences in mammographic density in GWAS (Lindstrom et al 2014) reinforces the potential interactions between estrogen exposure and breast cancer risk. Candidate genes linked to polymorphisms include the gene encoding ERα ( ESR1 ) and estrogen-responsive target genes (Amphiregulin, Insulin-like growth factor 1) as well as lymphocyte-specific factor 1 ( LSP1 ).…”
Section: Modifiers Of Estrogen Signaling --- Challenges and Opportunimentioning
confidence: 71%
“…Conversely, inhibition of signaling through estrogen receptors by Tamoxifen reduced mammographic density and was associated with decreased risk of subsequent breast cancer (Cuzick et al 2011). Identification of genes involved in estrogen signaling among the 11 loci associated with differences in mammographic density in GWAS (Lindstrom et al 2014) reinforces the potential interactions between estrogen exposure and breast cancer risk. Candidate genes linked to polymorphisms include the gene encoding ERα ( ESR1 ) and estrogen-responsive target genes (Amphiregulin, Insulin-like growth factor 1) as well as lymphocyte-specific factor 1 ( LSP1 ).…”
Section: Modifiers Of Estrogen Signaling --- Challenges and Opportunimentioning
confidence: 71%
“…Genotypes, mammographic density measures and information on conventional breast cancer risk factors were available for 10,727 self-reported women of European Ancestry from 13 studies described previously (4, 9, 11, 15). A summary of study design, sample sizes, mammographic and genotyping characteristics is given in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This confirmed prior associations found between the variant rs381798 (in the region of LSP1 ) (7, 8) and adjusted absolute and percent density and provided evidence for an association between rs10483813 (in the region of RAD51L1 ) and adjusted percent dense area (9). Two genome-wide association studies (GWAS) conducted by the Markers Of DEnsity (MODE) consortium found that there was an association between rs10995190 (in the ZNF365 locus), independently shown to be associated with breast cancer risk (10), and adjusted percent dense area, and weaker evidence for associations with the variants rs2046210 (in the region of ESR1 ) and rs3817198 (see above) (11). More recently, we identified novel loci associated with dense area (rs10034692 from AREG , rs703556 from IGF1 , rs7289126 from TMEM184B , rs17001868 from SGSME/MKL1 ), non-dense area (rs7816345 from 8p11.23 ), and percent density (rs186749 from PRDM6 , rs7816345 from 8p11.23 and rs7289126 from TMEM184B ) (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, breast cancer and mammographic density (Lindströ m et al, 2014), high density lipoprotein (HDL) and low density lipoprotein (LDL) (Global Lipids Genetics Consortium et al, 2013), or rheumatoid arthritis and irritable bowel disease (Liu et al, 2015;Okada et al, 2014) are all pairs of traits that share overlapping GWAS signals. Combining association signals at these pleiotropic regions may strengthen the signal from the causal variants that are impacting both traits.…”
Section: Introductionmentioning
confidence: 99%